The Participation of Community in Tourism Development of the Muara Jambi Temple Complex, Muaro Jambi Regency - Tirta Utama Sinuhaji; Suwardi Lubis; Asfriyati (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
The Muarajambi area is a national cultural preserve with an area of 3,981 hectares covering 9 villages in 2 sub-districts. This area has quite promising tourism potential. Tourism activities in the Muarajambi Temple area are centered in Muara Jambi Village. This is due to the fact that most of the restored temples are in this area. around the main temple complex. The development of tourism is pursued by the community by forming associations and organizations, so that it can help in developing tourism in the Muarajambi Temple area. Community participation in developing tourism in the Muarajambi Temple Area is mostly done through tourism conscious groups; in general community participation is influenced by two factors. The first factor is an internal factor, internal factors that influence the Group includes a strong desire of the community to participate, a sense of concern for Group members towards the younger generation, the age of the members involved in these groups are in the productive age, and the level of education of the management also influences their participation under construction. The second factor is an external factor, an external factor that influences community participation in tourism development in the Muara Jambi village, including the large support from the government regarding community involvement in activities that support tourism. However, the role of the Muaro Jambi Regency Government which has full authority over the development of this region has not yet had an influence in the process of developing the Muarajambi Temple Area.